Implementasi Shariah Value Added Terhadap Laporan Keuangan Entitas Syariah - Primantara, Ergy Restu; Triyuwono, Iwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to provide an overview of a comprehensive form of Sharia Value Added Statement in the form of a qualitative report by assigning justification in regard to most Sharia entities still applying accounting standards from PSAK, while PSAK itself still adopting entity theory. In addition, The Value Added Statement is an alternative for financial reporting in order to provide information related to the company’s contribution to stakeholders in a larger scope. The research employs a qualitative method with secondary data through an analytical tool in the form of Integrated Islamic Hyperstructuralism (HIT) which reconstructs and integrates normative values and empirical data. The results of this research include a qualitative form of The Sharia Value Added Statement which is modified from the Income Statement with the metaphor of zakat as a religious purification tool. Abstract Penelitian ini bertujuan untuk memberikan gambaran bentuk laporan Nilai Tambah Syariah yang lebih komprehensif dalam bentuk laporan kualitatif dengan membawa justifikasi bahwa sebagian besar lembaga syariah masih menggunakan standar akuntansi dari PSAK, sementara PSAK itu sendiri masih mengadopsi teori entitas. Selain itu, laporan nilai tambah menjadi alternatif bagi laporan keuangan agar menyajikan informasi terkait kontribusi perushaan bagi stakeholder secara luas. Metode penelitian yang digunakan adalah metode kualitatif dengan data sekunder melalui alat analisis Hiperstrukturalisme Islam Terpadu (HIT) yang merekonstruksi dan mengintegrasikan nilai-nilai normatif dan data empiris. Hasil dari penelitian ini yaitu bentuk kualitatif dari Laporan Nilai Tambah Syariah yang dimodifikasi dari Laporan Laba Rugi dengan metafora zakat sebagai alat penyucinya.